2018
DOI: 10.15561/20755279.2019.0403
|View full text |Cite
|
Sign up to set email alerts
|

Role of sports activities in developing the important life skill of decision making; a psychological perspective

Abstract: Purpose:It is generally believed that sports can play an important role in developing life skills and positive youth development. The purpose of this study was to determine the views of Gomal University students’ athletes on the role that sports played in developing the important life skill of decision making. The time management, planning, dealing with adversity and adapting new situation were taken as decision-making skills. Materials:A sample of n=375 (male=334, female=41 completed questionnaires. The resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…When they were 12 years old, girls who played sports regularly had better bone mineral density, as well as decreased cardiovascular risk, overweight, and obesity (Maciałczyk-Paprocka et al, 2017). Parents must encourage their children to participate in sports because sports participation always support students in improving their educational performance, which is the main aim of university sports (Khan, Khan, Arif & Khan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When they were 12 years old, girls who played sports regularly had better bone mineral density, as well as decreased cardiovascular risk, overweight, and obesity (Maciałczyk-Paprocka et al, 2017). Parents must encourage their children to participate in sports because sports participation always support students in improving their educational performance, which is the main aim of university sports (Khan, Khan, Arif & Khan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pada dasarnya aspek life skill ini bukan sekedar pengetahuan teknik atau keterampilan, tetapi lebih berorientasi pada sikap mental melalui proses diri dengan praktik dan pengalaman karena dorongan motivasi dari diri sendiri PHYTANZA et al, (2018). Oleh karena itu, pendapat dari Khan et al, (2019) guru sangat berperan penting dalam menanamkan sikap mental siswa ini, melalui proses pembelajaran. Untuk mengimplementasikan kedua aspek tersebut, guru PPKn harus memahami betul keduanya, sehingga ketika penyampaian materi akan terintegrasikan dalam proses pembelajaran Makmun, (2017).…”
Section: Hasil Dan Pembahasanunclassified
“…In Pakistani society, sports are also deeply embedded (Khan, Ahmed & Abid, 2016). There were very minimums chances for the masses to take part in sports after the independence of Pakistan; on the other hand, have risen in popularity because of the enhanced free time brought about by industrialization and remained an integral part of the culture of Pakistan (Khan et al, 2019). They concluded that thousands of individuals from different fields of life engage in multiple athletics events, invest millions of money in sports gear, and attend and enjoy sports activities as supporters as well as viewers.…”
Section: Introductionmentioning
confidence: 99%
“…The Pakistan Sports Board (PSB), Pakistan Olympic Association (POA), Ministry of Inter-Provincial Coordination (IPC) and several other institutions at the provincial level are the principal organization for controlling and managing sports events at national as well as international levels. Such organizations are striving to establish standards in Pakistan for athletic events that are similar to international standards of sports events (Khan et al, 2019). The Pakistan Olympic Association (POA), which was established in 1948, is in charge of overseeing and sponsoring provincial sports boards.…”
Section: Introductionmentioning
confidence: 99%